Two cases of hepatic adenomas in patients with wolf‐hirschhorn syndrome: A new rare complication?. Issue 7 (21st May 2013) - Prunotto, Giulia; Cianci, Paola; Cereda, Anna; Scatigno, Agnese; Fossati, Chiara; Maitz, Silvia; Biondi, Andrea; Selicorni, Angelo
Abstract Wolf–Hirschhorn syndrome (WHS) is a rare microdeletion syndrome associated with a characteristic facial appearance, failure to thrive, psychomotor delays, and various major malformations of internal organs; many medical complications have been described (feeding difficulties, epilepsy, hearing problems). Benign or malignant oncologic problems are not a typical feature of the natural history of these patients. We report on two patients with WHS patients in whom hepatic adenoma (HA) were diagnosed during adolescence. The clinical evolution of liver involvement was different between the two. We discuss the possibility of considering HA as a rare medical problem in the follow‐up of WHS patients. © 2013 Wiley Periodicals, Inc.